Composite positive electrode material and preparation method thereof, positive plate and lithium ion battery

Through the carbon coating method combined with preburning and crushing and fluidization processes, the conductivity and cycle stability of lithium iron phosphate materials are improved, and the problems of poor conductivity and iron dissolution in the prior art are solved, thereby achieving high conductivity and low conductivity Resistivity composite cathode material.

CN119252883APending Publication Date: 2025-01-03广州融捷能源科技有限公司
View PDF 0 Cites 8 Cited by

Patent Information

Application Number
CN202411313763.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The electronic conductivity and ionic conductivity of existing lithium iron phosphate materials are low, resulting in limited electrochemical performance and low graphitization of carbon coating, which can easily lead to poor conductivity of lithium iron phosphate and increased iron dissolution, affecting cycling performance. .

Method used

Using a combination of pre-fired crushing and fluidization processes, the graphitization degree of the carbon cladding layer is controlled to be 0.2-0.9, forming a uniform and complete carbon layer, improving conductivity and suppressing iron dissolution, and preparing a resistivity of 0.1-10Ω ·cm composite positive electrode material.

Benefits of technology

It significantly improves the conductivity and cyclic stability of the composite positive electrode material, reduces the resistivity, reduces the iron dissolution and magnetic material content, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252883A_ABST
    Figure CN119252883A_ABST
Patent Text Reader

Abstract

The invention discloses a composite positive electrode material and a preparation method thereof, a positive plate and a lithium ion battery. The composite positive electrode material comprises lithium iron phosphate and a carbon coating layer coating the surface of the lithium iron phosphate, wherein the integral intensity ratio ID / IG of a D peak to a G peak of the carbon coating layer in a Raman spectrum is 0.2-0.9, and the resistivity of the composite positive electrode material is 0.1-10 omega.cm. According to the preparation method, the graphitization degree of the carbon coating layer is controlled within a proper range (ID / IG is 0.2-0.9), so that good conductivity is ensured, and structural instability caused by excessive graphitization is avoided. The moderate graphitization degree is beneficial to formation of an ordered carbon layer structure, provides more electron transport channels and reduces the potential barrier of electron migration, so that the conductivity of the composite material is greatly improved, and the resistivity is reduced to an excellent level of 0.1-10 omega.cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a composite positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion battery is a secondary battery system that uses two different lithium-intercalation compounds that can reversibly intercalate and deintercalate lithium ions as positive and negative electrodes. With its advantages of high specific capacity, long cycle life, and low self-discharge, it is widely used in mobile phones, portable computers, camcorders, cameras, electric vehicles, energy storage, and other fields. Lithium iron phosphate is used in pure electric buses, energy storage, and other fields due to its high safety performance, good cycle life, and environmental friendliness.

[0003] Conventional lithium iron phosphate has low electronic and ionic conductivity, which greatly affects the electrochemical performance. Carbon coating, also known as carbon doping, is an effective method to improve the conductivity of lithium iron phosphate. However, the carbon layer currently coated on the surface of lithium iron phosphate materials is obtained by high-temperature cracking of organic matter, and the degree of graphitization of the formed carbon layer is low. At the same time, the lithium iron phosphate agglomerates after coating are easily damaged after air flow crushing, which will eventually cause poor conductivity of lithium iron phosphate and increased iron dissolution, resulting in the capacity of lithium iron phosphate and impaired storage and cycle performance.

[0004] Therefore, it is necessary to develop a composite positive electrode material with high conductivity and low resistivity. Summary of the invention

[0005] The purpose of the present invention is to provide a composite positive electrode material with high conductivity and low resistivity in view of the deficiencies of the prior art.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A composite positive electrode material, comprising lithium iron phosphate and a carbon coating layer coated on the surface of the lithium iron phosphate; wherein the integral intensity ratio of the D peak and the G peak of the carbon coating layer in the Raman spectrum is D / I G The resistivity of the composite positive electrode material is 0.1-10Ω·cm.

[0008] Preferably, the mass of the carbon coating layer accounts for 0.1-2% of the total mass of the composite positive electrode material.

[0009] Preferably, the magnetic substance content of the composite positive electrode material is 8-15 ppb.

[0010] In addition, the present invention also provides a method for preparing a composite positive electrode material, comprising the following steps:

[0011] S1. After mixing the carbon source, the iron source and the phosphorus source to obtain a mixed material, water is added to prepare a mixed water slurry, and the precursor slurry is obtained after sand grinding;

[0012] S2, spray-drying the precursor slurry, and then heat-treating it under an inert atmosphere to obtain lithium iron phosphate;

[0013] S3, the lithium iron phosphate is air flow-pulverized and then introduced into a reactor, an inert atmosphere is introduced, the temperature is increased, and then an organic gas is introduced to perform a fluidized carbon coating reaction, after the reaction is completed, the introduction of the organic gas is stopped, and the temperature is continued to be increased for heat treatment to obtain the composite positive electrode material.

[0014] Preferably, in step S1, the mass of the carbon source accounts for 0.1-3% of the total mass of the iron source, the phosphorus source and the lithium source.

[0015] Preferably, in step S1, the molar ratio of Fe, P and Li in the mixed material is (0.9-1.1):(1.0-1.06):(1.0-1.1), and the particle size D of the particles in the precursor slurry is 50 0.2-0.8μm, D 90 <3μm.

[0016] Preferably, in step S2, the heat treatment temperature is 400-600°C, the heating rate is 1-5°C / min, and the heat treatment time is 1-5h.

[0017] Preferably, in step S3, the particle size of the lithium iron phosphate after airflow pulverization is D 10 ≥0.3μm, 0.6μm≤D 50 ≤1.5μm, D 90 ≤5μm, D 99 ≤15μm; the carbon coating reaction temperature is 500-700℃, and the reaction time is 0.1-0.5h; the heat treatment temperature is 600-900℃, and the heat treatment time is 1-6h; the volume ratio of the inert gas to the organic gas is (50-99): (1-50).

[0018] In addition, the present invention also provides a positive electrode sheet made from the positive electrode material mentioned above.

[0019] In addition, the present invention also provides a lithium-ion battery, including a battery core wound by a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell encapsulating the battery core and the electrolyte, wherein the positive electrode sheet is made of the above-mentioned positive electrode material.

[0020] Compared with the prior art, the beneficial effects of the present invention are:

[0021] 1) The present invention controls the graphitization degree of the carbon coating layer within a suitable range (I D / IG The graphitization degree is 0.2-0.9), which not only ensures good conductivity, but also avoids structural instability caused by excessive graphitization. The moderate graphitization degree is conducive to the formation of an ordered carbon layer structure, providing more electron transmission channels and reducing the potential barrier of electron migration, thereby greatly improving the conductivity of the composite material and reducing the resistivity to an excellent level of 0.1-10Ω·cm.

[0022] 2) The present invention can significantly improve the coating uniformity and integrity of the carbon layer through the carbon coating method that combines pre-burning crushing and fluidization process. Pre-burning crushing can remove moisture and gas adsorbed on the surface of lithium iron phosphate, increase surface active sites, and facilitate the adsorption of carbon precursors; fluidized carbon coating can realize gas-solid homogeneous reaction, so that the carbon precursor is evenly pyrolyzed and deposited on the surface of the particles to form a dense and complete coating layer; the uniform and complete carbon coating layer can not only effectively inhibit the iron dissolution of the material, but also provide a more optimized channel for electron transmission, and at the same time, it can also effectively inhibit the erosion of the electrolyte on the lithium iron phosphate particles and improve the cyclic stability of the material.

[0023] 3) The carbon coating layer of the composite positive electrode material provided by the present invention is uniformly coated and has good integrity, a high degree of graphitization, and the composite positive electrode material has low resistivity and excellent conductivity. The present invention adopts a fluidized process carbon coating after pre-sintering and crushing the lithium iron phosphate material, so as to achieve a lower iron dissolution amount and a lower magnetic substance content of the composite positive electrode material particles, which is beneficial to improving the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a Raman spectrum of the composite positive electrode material of Example 1 of the present invention.

[0025] Figure 2 This is a Raman spectrum of the composite positive electrode material of Example 2 of the present invention.

[0026] Figure 3 This is a Raman spectrum of the composite positive electrode material of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] According to a first aspect of the present application, the present application provides a composite positive electrode material, including lithium iron phosphate and a carbon coating layer coated on the surface of the lithium iron phosphate;

[0029] The integrated intensity ratio of the D peak and the G peak of the carbon coating layer in the Raman spectrum is D / I G The resistivity of the composite positive electrode material is 0.1-10Ω·cm, for example, 0.1Ω·cm, 0.5Ω·cm, 1Ω·cm, 2Ω·cm, 3Ω·cm, 4Ω·cm, 5Ω·cm, 6Ω·cm, 7Ω·cm, 8Ω·cm, 9Ω·cm, 10Ω·cm.

[0030] In some embodiments, the mass of the carbon coating layer accounts for 0.1-2% of the total mass of the composite positive electrode material, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%. Controlling the mass proportion of the carbon coating layer to 0.1-2% can significantly improve the conductivity while retaining the high specific capacity of lithium iron phosphate to the maximum extent. Too high a carbon content will reduce the proportion of active materials in the positive electrode material and affect the energy density; while too low a carbon content will not form an effective conductive network. A carbon content of 0.1-2% achieves the best balance between the two, ensuring the high specific capacity of the composite material while improving the conductivity.

[0031] In some embodiments, the magnetic substance content of the composite positive electrode material is 8-15 ppb, for example, 8 ppb, 9 ppb, 10 ppb, 11 ppb, 12 ppb, 13 ppb, 14 ppb, or 15 ppb.

[0032] According to a second aspect of the present application, the present application provides a method for preparing a composite positive electrode material, comprising the following steps:

[0033] S1. After mixing the carbon source, the iron source and the phosphorus source to obtain a mixed material, water is added to prepare a mixed water slurry, and the precursor slurry is obtained after sand grinding;

[0034] S2, spray-drying the precursor slurry, and then heat-treating it under an inert atmosphere to obtain lithium iron phosphate;

[0035] S3, the lithium iron phosphate is air flow-pulverized and then introduced into a reactor, an inert atmosphere is introduced, the temperature is increased, and then an organic gas is introduced to perform a fluidized carbon coating reaction, after the reaction is completed, the introduction of the organic gas is stopped, and the temperature is continued to be increased for heat treatment to obtain the composite positive electrode material.

[0036] In some embodiments, in step S1, the mass of the carbon source accounts for 0.1-3% of the total mass of the iron source, the phosphorus source and the lithium source, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%. When the carbon content is too low, it is easy to cause insufficient uniformity and integrity of the carbon coating, and when the carbon content is too high, the specific capacity of the composite material will be damaged.

[0037] In some embodiments, in step S1, the molar ratio of Fe, P and Li in the mixed material is (0.9-1.1): (1.0-1.06): (1.0-1.1). When the iron content is too high, the phosphorus content is too low and the lithium content is too low, magnetic substances or elemental iron are easily produced, which brings safety hazards to subsequent applications; when the iron content is too low, the phosphorus content is too high and the lithium content is too high, the particles will grow excessively, resulting in a longer solid phase diffusion distance of lithium ions, thereby affecting the material's specific capacity.

[0038] In some embodiments, in step S1, the particle size D of the particles in the precursor slurry is 50 0.2-0.8 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm; D 90 <3μm, for example, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm. 50 When the particle size is too large, it will lead to insufficient reaction during the sintering process, affecting the purity of the produced lithium iron phosphate; when the grinding particle size is too small, it will cause the particles to fuse and become larger during the sintering process. The larger the particles, the longer the solid phase diffusion distance of lithium ions, which is not conducive to the electrical properties of the material.

[0039] In some embodiments, in step S1, the solid content of the mixed water slurry is 30-60%, for example, 30%, 40%, 50%, or 60%.

[0040] In some embodiments, in step S1, the carbon source includes an organic carbon source, and the organic carbon source includes at least one of glucose, polyethylene glycol, sucrose, Tween, polyvinyl alcohol, polyvinyl pyrrolidone or starch.

[0041] In some embodiments, in step S2, the heat treatment temperature is 400-600°C, for example, 400°C, 500°C, 600°C; the heating rate is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min; the heat treatment time is 1-5h, for example, 1h, 2h, 3h, 4h, 5h. When the heat treatment temperature is too low, the organic carbon source is not fully cracked, affecting the subsequent graphitization; when the heat treatment temperature is too high, it will lead to unnecessary increase in energy consumption.

[0042] In some embodiments, in step S3, the organic gas is at least one of methane, ethylene, acetylene, and propylene.

[0043] In some embodiments, in step S3, the inert atmosphere is at least one of helium, neon, argon, krypton, xenon and radon.

[0044] In some embodiments, in step S3, the air velocity of the fluidized carbon coating is 1-5000 km / h, the air velocity of the inert atmosphere and the organic gas is 0.005-1 m / s, and the bed density in the reactor is maintained at 500-800 kg / m 3 .

[0045] In some embodiments, in step S3, the heat treatment air velocity is 1-5000 km / h, the air velocity of the inert atmosphere is 0.005-1 m / s, and the bed density in the reactor is maintained at 500-800 kg / m 3 .

[0046] In some embodiments, in step S3, the particle size of the lithium iron phosphate after airflow pulverization is D 10 ≥0.3μm, 0.6μm≤D 50 ≤1.5μm, D 90 ≤5μm, D 99 ≤15μm; if the particle size is too small, it will be difficult to disperse or unable to disperse during the processing, resulting in the inability to coat or an increased coating defect rate; if the particle size is too large, it will easily lead to poor electrical properties of the material.

[0047] In some embodiments, the carbon coating reaction temperature is 500-700°C, for example, it can be 500°C, 550°C, 600°C, 650°C, 700°C, and the reaction time is 0.1-0.5h, for example, it can be 0.1h, 0.2h, 0.3h, 0.4h, 0.5h; the heat treatment temperature is 600-900°C, for example, it can be 600°C, 650°C, 700°C, 750°C, 800°C, 900°C, and the heat treatment time is 1-6h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h; the volume ratio of the inert gas to the organic gas is (50~99): (1~50), for example, it can be 50:50, 60:40, 70:30, 80:20.

[0048] According to a third aspect of the present application, the present application provides a positive electrode sheet made from the above-mentioned composite positive electrode material.

[0049] According to the fourth aspect of the present application, the present application provides a lithium-ion battery, comprising a battery cell formed by winding a negative electrode sheet, a positive electrode sheet and a separator, an electrolyte, and a shell that encapsulates the battery cell and the electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet.

[0050] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0051] Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for lithium-ion batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to copper foil.

[0052] The separator can be any material suitable for secondary battery separators in the art, for example, it can be a combination of one or more of, but not limited to, polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0053] The lithium-ion battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0054] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0055] Example 1

[0056] (1) Preparation of composite cathode materials

[0057] S1. Mix 150.8g of iron phosphate, 2g of ammonium phosphate, 38g of lithium carbonate and 5g of glucose to prepare a water-based slurry with a solid content of 40%, and then grind to D 50 0.45μm, D 90 <2μm, and the precursor slurry is obtained;

[0058] S2, drying the precursor slurry in a spray drying tower, controlling the spray drying inlet temperature at 250°C and the outlet temperature at 105°C to obtain a dried precursor powder; heating the precursor powder obtained after spray drying to 550°C under nitrogen protection at a heating rate of 3°C / min for 5h to obtain lithium iron phosphate;

[0059] S3, 10g lithium iron carbonate is air flow crushed, and the particle size after crushing is D 10 0.3~0.33μm, 0.8μm≤D 50 ≤1.0μm, D 90 ≤3μm, D 99 ≤8μm; put the crushed lithium iron phosphate into a vertical fluidized bed, first introduce 1.5L / min nitrogen, raise the temperature to 600℃, then introduce 1.5L / min methane, turn off the methane after 30 minutes, keep warm at 600℃ for 20 minutes, then raise the temperature to 800℃, continue heat treatment for 5 hours, cool to room temperature and take out to obtain a composite positive electrode material.

[0060] (2) Preparation of positive electrode

[0061] The composite positive electrode material, PVDF and conductive agent prepared above were mixed uniformly in a mass ratio of 96:2:2 to prepare a positive electrode slurry. The obtained positive electrode slurry was coated on an aluminum foil current collector, dried at 105° C., and then rolled to obtain a positive electrode sheet.

[0062] (3) Preparation of negative electrode sheet

[0063] Graphite, conductive agent carbon nanotubes, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose were stirred and mixed in deionized water at a mass ratio of 97.2:1.2:0.8:0.8. After being mixed evenly, the negative electrode slurry was coated on Cu foil, baked, rolled, and cut into strips to obtain a negative electrode sheet.

[0064] (4) Preparation of diaphragm

[0065] Polyethylene (PE) polymer film is used as the isolation membrane.

[0066] (5) Preparation of electrolyte

[0067] Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0068] (6) Preparation of batteries

[0069] The prepared positive electrode sheet, negative electrode sheet and separator are wound to obtain a battery cell, the battery cell is put into a shell, the electrolyte is injected into the battery shell, packaged, formed and divided into volumes, and a lithium-ion battery is obtained.

[0070] Example 2

[0071] Different from Example 1, the preparation of the composite positive electrode material in this example is as follows:

[0072] S1. Mix 150.8g of iron phosphate, 3g of ammonium phosphate, 38.5g of lithium carbonate and 6g of polyvinyl pyrrolidone to prepare a water-based slurry with a solid content of 40%, and then grind to D 50 0.4μm, D 90 <2μm, and the precursor slurry is obtained;

[0073] S2, drying the precursor slurry in a spray drying tower, controlling the spray drying inlet temperature at 250°C and the outlet temperature at 105°C to obtain a dried precursor powder; heating the precursor powder obtained after spray drying to 600°C at a heating rate of 5°C / min for 2h under nitrogen protection to obtain lithium iron phosphate;

[0074] S3, 10g lithium iron carbonate is air flow crushed, and the particle size after crushing is D 10 0.33~0.35μm, 0.8μm≤D 50 ≤1.0μm, D 90 ≤3μm, D 99 ≤8μm; put the crushed lithium iron phosphate into a vertical fluidized bed, first introduce 1.5L / min nitrogen, raise the temperature to 600℃, then introduce 1.0L / min propylene, turn off the propylene after 10 minutes, keep the temperature at 600℃ for 20 minutes, then raise the temperature to 850℃, continue heat treatment for 3 hours, cool to room temperature and take out to obtain a composite positive electrode material. The rest is the same as Example 1, which will not be repeated here.

[0075] Example 3

[0076] Different from Example 1, the preparation of the composite positive electrode material in this example is as follows:

[0077] S1. 150.8 g of iron phosphate, 38.5 g of lithium carbonate, 18 g of 4 wt% aqueous graphene slurry, and 16 g of polyvinyl pyrrolidone were mixed to prepare an aqueous slurry with a solid content of 40%, and then sand-milled to D 50 0.4μm, D 90 <2μm, and the precursor slurry is obtained;

[0078] S2, drying the precursor slurry in a spray drying tower, controlling the spray drying inlet temperature at 250°C and the outlet temperature at 105°C to obtain a dried precursor powder; heating the precursor powder obtained after spray drying to 750°C under nitrogen protection at a heating rate of 5°C / min for 9 hours to obtain lithium iron phosphate;

[0079] S3, 10g lithium iron carbonate is air flow crushed, and the particle size after crushing is D 10 0.35~0.37μm, 1.0μm≤D 50 ≤1.2μm, D 90 ≤3μm, D 99 ≤8μm; put the crushed lithium iron phosphate into a vertical fluidized bed, first introduce 1.5L / min nitrogen, raise the temperature to 600℃, then introduce 1.2L / min acetylene, turn off the acetylene after 10 minutes, keep it at 700℃ for 20 minutes, then raise the temperature to 800℃, continue heat treatment for 5 hours, cool to room temperature and take out to obtain a composite positive electrode material.

[0080] The rest is the same as Example 1 and will not be described again here.

[0081] Example 4

[0082] Different from Example 1, the preparation of the composite positive electrode material in this example is as follows:

[0083] S1. 150.8 g of iron phosphate, 38.5 g of lithium carbonate, 3 g of ammonium phosphate, 10 g of 4 wt% aqueous carbon nanotube slurry, 6 g of 4 wt% aqueous graphene slurry, 10 g of polyvinyl pyrrolidone and 7 g of glucose were prepared into an aqueous slurry with a solid content of 40%, and then sand-milled to D 50 0.4μm, D 90 <2μm, and the precursor slurry is obtained;

[0084] S2, drying the precursor slurry in a spray drying tower, controlling the spray drying inlet temperature at 250°C and the outlet temperature at 105°C to obtain a dried precursor powder; heating the precursor powder obtained after spray drying to 750°C under nitrogen protection at a heating rate of 5°C / min for 9 hours to obtain lithium iron phosphate;

[0085] S3, 10g lithium iron carbonate is air flow crushed, and the particle size after crushing is D 10 0.37~0.40μm, 1.0μm≤D 50 ≤1.2μm, D 90 ≤3μm, D 99≤8μm; put the crushed lithium iron phosphate into a vertical fluidized bed, first introduce 1.5L / min nitrogen, raise the temperature to 600℃, then introduce 1.2L / min acetylene, turn off the acetylene after 10 minutes, keep it at 700℃ for 20 minutes, then raise the temperature to 800℃, continue heat treatment for 5 hours, cool to room temperature and take out to obtain a composite positive electrode material.

[0086] The rest is the same as Example 1 and will not be described again here.

[0087] Comparative Example 1

[0088] Different from Example 1, the preparation of the composite positive electrode material in this comparative example is as follows:

[0089] S1. Prepare 150.8g of iron phosphate, 38g of lithium carbonate, 2g of ammonium phosphate and 20g of glucose into a 40% solid content aqueous slurry, and then grind to D 50 0.45μm, D 90 <2μm, and the precursor slurry is obtained;

[0090] S2. Dry the precursor slurry in a spray drying tower, control the spray drying inlet temperature at 250°C, and the outlet temperature at 105°C to obtain a dried precursor powder; heat the precursor powder obtained after spray drying to 750°C at a heating rate of 3°C / min under nitrogen protection for 9 hours to obtain lithium iron phosphate with a surface coated with a carbon layer.

[0091] The rest is the same as Example 1 and will not be described again here.

[0092] Comparative Example 2

[0093] Different from Example 1, the preparation of the composite positive electrode material in this comparative example is as follows:

[0094] S1. 150.8 g of iron phosphate, 2 g of ammonium phosphate, 38 g of lithium carbonate and 5 g of glucose were mixed to prepare a water-based slurry with a solid content of 40%, and then sand-milled to a D50 of 0.45 μm and a D90 of <2 μm to obtain a precursor slurry;

[0095] S2, drying the precursor slurry in a spray drying tower, controlling the spray drying inlet temperature at 250° C. and the outlet temperature at 105° C. to obtain dried lithium iron phosphate;

[0096] S3. 10g of lithium iron carbonate is subjected to air flow crushing. After crushing, the particle size D10 is 0.3-0.33μm, 0.8μm≤D50≤1.0μm, D90≤3μm, and D99≤8μm. The crushed lithium iron phosphate is placed in a vertical fluidized bed, and first 1.5L / min nitrogen is introduced, the temperature is raised to 600℃, and then 1.5L / min methane is introduced. After 30 minutes, the methane is turned off, and the temperature is kept at 600℃ for 20 minutes and then raised to 800℃. The heat treatment is continued for 5 hours, and the composite positive electrode material is obtained after cooling to room temperature.

[0097] The rest is the same as Comparative Example 1 and will not be described again.

[0098] Performance Testing

[0099] The composite positive electrode materials prepared in the above examples and comparative examples were tested, and the obtained physicochemical indicators are shown in Table 1 below.

[0100] (1) Raman spectroscopy test: The test was performed using a Raman spectrometer (SENTERRA) with a laser wavelength of 488.01 nm, a laser power of 0.15 mW, and an integration time of 60 s.

[0101] (2) Material resistivity test: An electronic balance (with an accuracy of 0.0001 g) and a powder resistivity tester FT-300 were used to perform the test at a pressure of 30 MPa.

[0102] (3) Iron dissolution test: The test was performed using an electronic balance (with an accuracy of 0.0001 g), ICP-OES, and a PerkinElmer Avio 200 instrument.

[0103] (4) Magnetic material test: A graphite digester (Labtech ED54), a magnetic bar (6000GS), an electronic balance (accuracy: 0.0001 g), an ultrasonic cleaner (53 kHz, 360 W), a roller mixer (rotation speed can be set in the range of 60 r / min to 100 r / min), an ICP-OES, and a PerkinElmer Avio 200 instrument were used.

[0104] Table 1

[0105]

[0106] From the comparison of the test data of the embodiment and the comparative example in Table 1 above, it can be seen that when the positive electrode material precursor contains only a carbonate phase precursor and does not contain a hydroxide phase precursor, the cycle retention rate does not change significantly, but the charge and discharge capacity decreases significantly; when the positive electrode material precursor contains only a hydroxide phase precursor and does not contain a carbonate phase precursor, the charge and discharge capacity does not change significantly, but the cycle retention rate decreases significantly.

[0107] It can be seen from Examples 1-4 and Comparative Example 1 in Table 1 above that, compared with the method of carbon coating by fluidized process after pre-burning and crushing provided in the present application, when the composite positive electrode material is not subjected to airflow crushing and carbon coating, the resistivity, iron dissolution content and magnetic substance content of the material are high. When the precursor is not subjected to crushing, the resistivity, iron dissolution content and magnetic substance content of the material are too high. The resistivity leads to excessive ohmic heat generated by the material in the battery, affecting the energy efficiency of the battery; the iron dissolution and magnetic substance are too large, affecting the safety performance and cycle performance of the battery.

[0108] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A composite positive electrode material, characterized in that: It comprises lithium iron phosphate and a carbon coating layer coated on the surface of the lithium iron phosphate; The integrated intensity ratio of the D peak and the G peak of the carbon coating layer in the Raman spectrum is D / I G The resistivity of the composite positive electrode material is 0.1-10Ω·cm.

2. The composite positive electrode material according to claim 1, characterized in that The mass of the carbon coating layer accounts for 0.1-2% of the total mass of the composite positive electrode material.

3. The composite positive electrode material according to claim 1, characterized in that: The magnetic substance content of the composite positive electrode material is 8-15 ppb.

4. A method for preparing a composite positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. After mixing the carbon source, the iron source and the phosphorus source to obtain a mixed material, water is added to prepare a mixed water slurry, and the precursor slurry is obtained after sand grinding; S2, spray-drying the precursor slurry, and then heat-treating it under an inert atmosphere to obtain lithium iron phosphate; S3, the lithium iron phosphate is air flow-pulverized and then introduced into a reactor, an inert atmosphere is introduced, the temperature is increased, and then an organic gas is introduced to perform a fluidized carbon coating reaction, after the reaction is completed, the introduction of the organic gas is stopped, and the temperature is continued to be increased for heat treatment to obtain the composite positive electrode material.

5. The method for preparing a composite positive electrode material according to claim 4, characterized in that: In step S1, the mass of the carbon source accounts for 0.1-3% of the total mass of the iron source, the phosphorus source and the lithium source, and the molar ratio of Fe, P and Li in the mixture is (0.9-1.1):(1.0-1.06):(1.0-1.1).

6. The method for preparing a composite positive electrode material according to claim 4, characterized in that: In step S1, the particle size D of the particles in the precursor slurry is 50 0.2-0.8μm, D 90 <3μm.

7. The method for preparing a composite positive electrode material according to claim 4, characterized in that: In step S2, the heat treatment temperature is 400-600°C, the heating rate is 1-5°C / min, and the heat treatment time is 1-5h.

8. The method for preparing a composite positive electrode material according to claim 4, characterized in that: In step S3, the particle size of lithium iron phosphate after air flow pulverization is D 10 ≥0.3μm, 0.6μm≤D 50 ≤1.5μm, D 90 ≤5μm, D 99 ≤15μm; the carbon coating reaction temperature is 500-700℃, and the reaction time is 0.1-0.5h; the heat treatment temperature is 600-900℃, and the heat treatment time is 1-6h; the volume ratio of the inert gas to the organic gas is (50-99): (1-50).

9. A positive electrode sheet, characterized in that: The composite positive electrode material comprises the composite positive electrode material according to any one of claims 1 to 3.

10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Lithium ion secondary battery, battery device, and power device

    CN120033312A

  • Lithium-ion secondary battery, battery device, and electric device

    CN120033312B

  • Lithium ion secondary battery, battery device, power utilization device, preparation method of positive active material and preparation method of positive pole piece

    CN120109156A

  • Metal composite lithium iron phosphate solid-phase deposition coated lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN120483081A

  • Sodium-ion battery monomer, preparation method thereof, battery device and power utilization device

    CN121583994A